Exam Anxiety among University Students - Anum Zahra; Dr. Sajid Mahmood Alvi; Parsa Muazzam (Journal of Management Practices, Humanities and Social Sciences, 2022)
This study was conducted to assess the level of exam anxiety among university students of KIU during exams and also analysis the difference in anxiety between male and female students. A sample size of 200 (97 female & 103 males) students was selected from ten KIU departments with respect to age 19-28 years and by stratified Convenient sampling. Westside Test Anxiety Scale applied on participants. Data were analyzed by using SPSS version 20.0. The results of the study show that 17% students have comfortable low exam anxiety, 32% normal test anxiety, 12% high normal test anxiety, 28% moderately high, 10% have high test anxiety, While 1% have extremely high anxiety. However, when compared with cutoff score, studied sample reported high level of exam anxiety. The result also showed no significant difference in anxiety level among students of different departments in KIU, and there is no gender difference in exam anxiety; male and female students have equal exam anxiety. However, students studying semester significantly influenced their reported exam anxiety.